Large emissions of CO2 and CH4 due to active-layer warming in Arctic tundra - Margaret S. Torn; Rose Z. Abramoff; Lydia J. S. Vaughn; Oriana E. Chafe; J. Bryan Curtis; Biao Zhu (Nature Communications)
Abstract Climate warming may accelerate decomposition of Arctic soil carbon, but few controlled experiments have manipulated the entire active layer. To determine surface-atmosphere fluxes of carbon dioxide and methane under anticipated end-of-century warming, here we used heating rods to warm (by 3.8 °C) to the depth of permafrost in polygonal tundra in Utqiaġvik (formerly Barrow), Alaska and measured fluxes over two growing seasons. We show that ecosystem respiration is ~30% higher in warmed plots than in control plots (0.99 μmol m−2 s−1 versus 0.67 μmol m−2 s−1, p < 0.0001, n = 79). Additionally, the observed temperature sensitivity (Q10 of 2.8) is higher than that imposed for soil in Earth system models or reported by arctic experiments warming only the surface. A shoulder-season warming experiment revealed that rapid snow melt, which is becoming a more common event, can result in large methane emissions that may have otherwise been oxidized to carbon dioxide. Thus, warming promotes greenhouse gas emissions from the whole, deepening active layer and may contribute to climate change amplification.